HIGH SENSITIVITY 0.5 TO 19.5 GHZ RECEIVER WITH 1.1-GHZ INSTANTANEOUS BANDWIDTH - Volkov, V. A.; Vavriv, D. M.; Bulakh, E. V.; Kravtsov, A. A. (Видавничий дім «Академперіодика», 2015)
A wideband high sensitivity microwave receiver operating within 0.5 to 19.5 GHz and providing a 1.1-GHz instantaneous bandwidth is described. The receiver shows a noise figure as low as 10 dB and the input third-order intercept point up to 10 dBm as well. Also, the receiver is characterized by a low spurious response and extremely low residual phase noise, too. Essential design principles of the receiver are given and discussed.Keywords: receiver, wideband, low-noise, microwaveManuscript submitted 09.09.2014Radio phys. radio astron. 2014, 19(4): 375-380 REFERENCES1. NERI, F., 2006. Introduction to Electronic Defense Systems, 2nd ed. Artech House. 2. TSUI, J., 2005. Microwave Receivers With Electronic Warfare Applications. Corrected Reprint, Raleigh, NC: SciTech Publishing. 3. Multi-Carrier and Spread Spectrum Systems: From OFDM and MC-CDMA to LTE and WiMAX, 2nd Ed. – John Wiley & Sons Inc., 2008. 4. GOLDSMITH, A., 2005. Wireless Communications. New York: Cambridge University Press. 5. REMBOVSKY, A., ASHIKHMIN, A., KOZMIN, V., and SMOLSKIY, S. M., 2009. Radio Monitoring. Dordrecht, Heidelberg, London, New York: Springer. 6. SIMON, M., OMURA, J., SCHOLTZ, R., and LEVITT, B., 2001. Spread Spectrum Communications Handbook. New York, Chicago, San Francisco, Lisbon, London, Madrid, Mexico City, Milan, New Delhi, San Juan, Seoul, Singapore, Sydney, Toronto: McGraw-Hill Professional. 7. WICKS, M. C., MOKOLE, E. L., BLUNT, S. D., SCHNEIBLE, R. S., and AMUSO, V. J., 2011. Principles of Waveform Diversity and Design. Raleigh, NC: SciTech Publishing. 8. BEZVESILNIY, O. O., VAVRIV, D. M., VINOGRADOV, V. V., VOLKOV, V. A., and KOZHIN, R. V., 2012.Synthetic Aperture Radar Systems for Light-Weight Aircrafts. Uspehi sovremennoy radioelektroniki. no.12, pp. 53–61, (in Russian). 9. RUDERSDORFER, R., 2014. Radio Receiver Technology: Principles, Architectures and Applications. John Wiley & Sons Inc. 10. DRENTEA, C., 2010. Modern Communications Receiver Design and Technology. Artech House. 11. MARKI, F. and MARKI, C. T3 Mixer Primer, App. Note. Morgan Hill, CA: Marki Microwave. 12. TEPPATI, V., FERRERO, A., and SAYED, M., 2013. editors, Modern RF and Microwave Measurement. Techniques. New York: Cambridge University Press.